Patient-response to hospitalisation - Maureen Salmon (AOSIS, 1979)
Since that fateful moment in the Garden of Eden when our ancestor Adam was tempted to eat of the forbidden fruit, illness and disease entered man's existence. Primitive civilizations regarded disease as of supernatural origin and in the Middle Ages illness was interpreted as a manifestation of the will of God. With the evolution of modern medicine, hospitals have ceased to be primarily charitable institutions or refuges for the homeless and have become highly complex organisms directed at the highest possible standard of patient care. It is sad that in this striving towards maximal therapeutic efficiency, the understanding of the patient as a total person tends to suffer.